2012
DOI: 10.1093/jac/dks479
|View full text |Cite
|
Sign up to set email alerts
|

Tissue pharmacokinetics of ertapenem at steady-state in diabetic patients with leg infections

Abstract: Although total plasma concentrations of ertapenem were lower in diabetics than reported for healthy subjects, free interstitial tissue concentrations in diabetics were similar to those known from healthy volunteers. Penetration of ertapenem into the interstitium of inflamed tissue of diabetic feet was not impaired in spite of angiopathy. Daily doses of >1 g of ertapenem might be considered to optimize bactericidal effects in diabetic foot infections caused by moderately susceptible strains.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 27 publications
1
9
0
Order By: Relevance
“…The mean volume of distribution calculated by KinFIT was lower for MDR-TB patients than for the healthy volunteers, whereas the mean clearance was higher for the MDR-TB patients than for the healthy volunteers. Our observations are consistent with other studies that showed a lower drug exposure of ertapenem in patients with infectious diseases [23][24][25]. More surprising was the intervariability in AUC between patients with MDR-TB.…”
Section: Discussionsupporting
confidence: 93%
“…The mean volume of distribution calculated by KinFIT was lower for MDR-TB patients than for the healthy volunteers, whereas the mean clearance was higher for the MDR-TB patients than for the healthy volunteers. Our observations are consistent with other studies that showed a lower drug exposure of ertapenem in patients with infectious diseases [23][24][25]. More surprising was the intervariability in AUC between patients with MDR-TB.…”
Section: Discussionsupporting
confidence: 93%
“…It is shown that the introduction of ertapenem intravenously at a dose of 1.0 after 8 hours ego concentration, determined at a microdialysis in the soft tissues in patients with DFIs did not differ from the registered concentration in healthy volunteers [45].…”
Section: Malorodova Tn Pokrovskaya Tg каZаkоvа Ee Urojevskaymentioning
confidence: 86%
“…The ertapenem penetration into soft tissue adjacent to a foot infection in diabetic patients was well comparable to these results. The unbound AUC in tissue divided by the total drug AUC in plasma was 8.3% for healthy tissue and 9.5% for inflamed tissue (29). Assuming a protein binding of 90% in plasma, this would translate into unbound AUC ratios of approximately 83% and 95%, respectively.…”
Section: Discussionmentioning
confidence: 99%